Close Loop V/F Control of Voltage Source Inverter using Sinusoidal PWM, Third Harmonic Injection PWM and Space Vector PWM Method for Induction Motor - Sandeep Ojha; Ashok Kumar Pandey (Institute of Advanced Engineering and Science, 2016)
The aim of this paper to presents a comparative analysis of Voltage Source Inverter using Sinusoidal Pulse Width Modulation Method, Third Harmonic Injection Pulse Width Modulation Method and Space Vector Pulse Width Modulation Two level inverter for Induction Motor. In this paper we have designed the Simulink model of Inverter for different technique. An above technique is used to reduce the Total Harmonic Distortion (THD) on the AC side of the Inverter. The Simulink model is close loop. Results are analyzed using Fast Fourier Transformation (FFT) which is for analysis of the Total Harmonic Distortion. All simulation are performed in the MATLAB Simulink / Simulink environment of MATLAB.